Teaching Signal Processing Design for Effect Pedals: Making Signal Processing Tangible - V J Manzo; Ryan McKenna; Matthew Halper (Journal of the Association for Technology in Music Instruction, 2022)
Teaching digital audio processes and their uses in musical contexts is a challenging subject area for music technology instructors. While there are many books and resources that explain audio processes using diagrams and charts that merely require the reader to have modest skills in mathematics, computer science, or electrical engineering, these extra-musical subjects still pose great challenges for music students. Given the time and scope limitations implicit in a single semester, pedagogy for effects processes often has to be reduced to qualitative descriptions and audio examples. The more ambitious task of implementing such processes, realizing an algorithm via a plugin or a physical hardware pedal, is thus not always feasible. We have addressed this difficulty by creating an effect development kit including a software-based tool to facilitate rapid effect prototyping and guides for assembling hardware around a microcontroller. With these resources, students need only focus on understanding the specific audio process they wish to implement into an effect and then use these resources to realize the effect in a standalone device. This paper describes the open-source software and guides we have assembled in this kit, and our implementation of these resources with undergraduate students enrolled in a music technology course.
Keywords: electric guitar; effects; signal processing; stompboxes; max; interactive music systems; open-source; programmable microcontrollers; education resources